Antifungal and Plant Growth Promoting Characters of Siderophore Producing Bacteria - Mahebub, Sherasiya J.; Parmar, Preeti R.; Rajkumar, B. K.; Vekariya, V. K.; Sutahr, Kiran (International Journal of Economic Plants, 2025)
The experiment was conducted during January (2021–2022) at Main Cotton Research Station (MCRS), Navsari Agricultural University (NAU), Surat, Gujarat, India to study antifungal and plant growth promoting activities of siderophore producing bacteria isolated from cotton rhizosphere. Siderophore producing bacteria, coded as NAU-RPJ-54 was isolated from the cotton rhizospheric soil at Main Cotton Research Station (MCRS), Navsari Agricultural University (NAU). It showed 0.94 of zone index (ZI) and 66.24% siderophore unit (PSU) with Chrome Azurol Sulfonate (CAS) agar and liquid assay, respectively at 30±2°C for 72 hrs. Csaky’s assay and Thin Layer Chromatography (TLC) revealed that it possessed hydroxamate type of siderophore. Confrontation assay revealed 84.04% and 61.53% mycelium inhibition of Sclerotium rolfsii at 72 hrs and Fusarium oxysporium f.sp. Lycopersicon at seven days, respectively. In vitro studies of plant growth promoting activities showed that NAU-RPJ-54 produced indole acetic acid, cellulase, protease and HCN; it solubilized zinc, potash and phosphate. Further, salt tolerance test using nutrient agar prepared with different concentration viz. 100, 200, 400 and 600 mM of NaCl, CaCl2 and MgCl2 mixture at ratio of 3:2:1, respectively showed NAU-RPJ-54 was resistant to salt upto 600 mM. Microbiological characterization indicated that NAU-RPJ-54 might belong to Statphylococcus genus. NAU-RPJ-54 showed potential attractive attributes like siderophore production, antifungal activity and plant growth promoting traits. Further, comprehensive studies required to explore this bacterium in field conditions.